Thermal conductivity of aluminum oxide nanoparticles in an aqueous [HMIM]LS solution using transient hot wire method - Tanguilan, Glaiza Escobar (2012)
Colloidal suspensions of nanoparticles in base fluids commonly known as nanofluids, are found to have enhanced thermal properties especially thermal conductivity. Because of this enhancement, nanofluids find most of their applications in thermal management of several processes.On of the key issues with nanofluids is its stability. To adress this problem, surfactants are being used. A novel type of surfactant is the ionic liquid which has superior thermophysical properties including thermal conductivity, compared to common surfactants. This paper presents the thermal conductivity of dispersions of aluminum oxide nanoparticles (TEM <50) at low concentrations (0.25, 0.50 and 0.75 5 %v/v) in aqueous 1-hexyl-3-methylimidazolium lauryl sulfate (HMIMLS) solution measured using the transient hot-wire method. Results show up to 40% thermal conductivity enhancement can be achieved with 0.75% v/v Al2O3 in aqueous HMIMLS solution at 75 deg.C. Also, empirical models to describe the temperature and particle concentration effects on thermal conductivity enhancement are presented.
"10 April 2012."
Thesis (M.S. in Energy Engineering)--University of the Philippines, Diliman
Keywords: Thermal conductivity; Nanofluids; Aluminum oxide; Aqueous solutions